INDONESIAN EFL TEACHERS’ EXPERIENCES OF USING COPING STRATEGIES TO DEAL WITH STRESS AT WORK - Krisanti, Nadya Demes; Siti Masrifatul Fitriyah; Annur Rofiq (ELLTER Journal, 2024)
Teaching has been recognized as one of stressful occupations. In Indonesia, EFL teachers also perceive stress at work due to abundant responsibilities that they carry out. The use of coping strategies is essential to help them deal with stress at work. Therefore, this study aims to explore EFL teachers' experiences, especially the sources of their stress, the coping strategies used by EFL teachers, and the advantages and challenges of using those coping strategies. Using a narrative-based approach to explore their experiences, the findings show that there were 8 sources of EFL teacher’s stress at work. The coping strategies varied from five areas of: work demands, boredom, personal conflict, interpersonal conflict, and emotion. Those coping strategies were helpful to lessen the feeling of stress and resolve teachers’ problems at work. Despite those advantages, the teachers also mentioned that lack of me-time can be a challenge for the optimum use of the coping strategies. Meanwhile, social support from family and friends can contribute to help the teachers deal with their stress at work.